Analisis Campuran Agregat AC-BC dengan Substitusi Limbah Polyethylene Terephthalate dengan Filler Semen - Bintang, Audito; Hartatik, Nurani; Fatmawati, Laily Endah (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Indonesia generated 4.14 million tons of plastic waste in 2021, making it the second-largest plastic waste contributor in the world. One type of plastic, Polyethylene Terephthalate (PET), is particularly difficult to decompose and has negative environmental impacts. This study aims to analyze the use of PET waste in Asphalt Concrete–Binder Course (AC-BC) mixtures to improve pavement quality while reducing plastic waste. The method used involves analyzing the gradation of aggregate, asphalt, and PET waste mixtures based on the 2018 General Specifications of Bina Marga (Revision 2). PET waste was selected due to its high availability and durability. The results indicate that there is an ideal composition of aggregate, asphalt, and PET that meets the required gradation criteria. This study shows that PET waste can be utilized as a technically feasible asphalt mixture component and contributes to sustainable infrastructure development.